Long Term Experience in Patients With JIA-Associated Uveitis in a Large Referral Center - Marelli, Luca; Romano, Micol; Pontikaki, Irene; Gattinara, Maurizio Virgilio; Nucci, Paolo; Cimaz, Rolando; Miserocchi, Elisabetta (Frontiers in Pediatrics, 2021)
Objectives: to describe demographic, clinical and therapeutic findings of a large cohort of patients with JIA-associated uveitis in a nationwide referral pediatric rheumatology and uveitis center in Northern Italy. Methods: retrospective study of 125 patients with JIA-associated uveitis followed from 2009 to 2019. Demographic and rheumatologic features including JIA ILAR classification, age at onset, and laboratory data were recorded. Ocular findings collected were: anatomic location of uveitis, laterality, type, recurrence rate, visual acuity, ocular complications, and local therapy. Systemic therapy with conventional and biologic immunosuppressants, occurrence of adverse events, and duration of treatments were recorded. Results: 125 patients with JIA-associated uveitis were followed for a meantime of 9.2 (1.7) years. Oligoarticular JIA was present in 92.8% of patients and anterior uveitis in 96%. The most common ocular complications recorded in our sample were posterior synechiae (37.6%), cataract (20.8%), band keratopathy (19.2%), glaucoma (7.2%), and macular edema (5.6%). Conventional immunosuppressants were used in 75.2% of patients with a mean duration of 9.1 years ( 5.4), while biologics were administered in 47.2% of them for a period of 5.4 years. Adverse events (AE) were seen in 23% of patients being treated with Methotrexate, in 10.4% of patients treated with Adalimumab, in 38.5% of patients in therapy with Infliximab, and in 14.3% of patients being treated with Tocilizumab. No AE were reported in patients treated with Golimumab, Certolizumab, Abatacept and Rituximab. Conclusions: an aggressive treatment approach for patients with JIA-associated uveitis ensured a low number of ocular complications with a good safety profile.